A comparison between oral reading fluency in English and Bahasa Malaysia among primary 1 students - Azeryna, anak Mike (Universiti Malaysia Sarawak (UNIMAS), 2015)
Reading comprehension is important measure to identify whether the students understand their reading and learning process. The perfonnance oforal reading fluency is one of the factor affect the measure. In Malaysia, the main language used is Bahasa Malaysia and English is the second language. Therefore, this study intended to compare the perfonnance of oral reading fluency between English and Bahasa Malaysia among Primary 1 students. This study was involved 865 students from 11 randomly selected government schools. They are tested with their ability in oral reading fluency in both languages. This study is take place in Kuching, Sarawak. The result indicates students score well in Bahasa Malaysia than English. The average score in Bahasa Malaysia is bigger than in English. Meanwhile, the girls outperfonn boys in both languages. Then, students with English as their second language perfonn average in English oral reading fluency. The causes of these results are then identified and discussed.